The Implementation of Multicultural-based Islamic Education at State Junior High Schools - Indra Saputra (Nalar: Journal of Pedagogy and Society, 2020)
This study aims to determine the learning application of Islamic religious education with a multicultural perspective at State Junior High Schools in Siak Hulu District, Kampar. The focus of this research is to discuss how is the implementation of Islamic Religious Education material with a multicultural perspective? What methods are applied in learning Islamic Religious Education with a multicultural perspective? And how is the evaluation of Islamic Religious Education learning with a multicultural perspective in State Junior High Schools in Siak Hulu District, Kampar Regency. This research is a Qualitative Research, with a Case Study Approach. Data were collected by using observation, interviews, and documentation. Furthermore, the results of these techniques are selected in accordance with the focus of the study. To see the validity of the data, data triangulation technique was applied, and then it is continued with drawing conclusions. After that, thorough research was conducted on the implementation of Islamic religious education with a multicultural perspective at Junior High Schools id Siak Hulu District, Kampar Regency. It can be concluded that: the appropriate material for Islamic Education with a multicultural perspective is to reconcile the country with tolerance, with the aim of learning so that we can live in harmony in the life of the nation and state. To find out the level of understanding of students, it can be seen in the learning process of Islamic Religious Education with a multicultural perspective and can be measured by religious and social attitudes. Various kinds of discussion methods are used in learning Islamic Religious Education with a multicultural perspective with the aim of making learning more enjoyable and raise students’ enthusiasm, thereby making it easier for teachers and students to learn, by showing the behavior of students who respect each other, tolerance and mutual respect.